A Work study on twin oaks foods corporation marshmallow division - Guerrero, Geraldine; Reyes, Ronald Allan; Yu, Clarence; Yu, Lawrence (Diliman, Quezon City College of Engineering, 1992)
Twin Oaks Foods Corporation is a relatively new establishment. Its marshmallow division has been in operation for only around two (2) years yet it is surprisingly very efficient. The study team discovered through the course of their methods study that the company has rid itself of start-up problems usually associated with setting up a subsidiary manufacturing plant. Very few problems, like bottleneck operations, were discovered. With this in mind, the study team decided to concentrate more of its efforts on improving the present system which includes the production process and the working environment. It was discovered that output may be increased through an improved production process. In the study conducted on the Marshmallow division, it has been found that the working condition, packing and sorting methods, and the layout can be modified in order to improve the workers' efficiency, save time and energy, and simplify the flow of materials, respectively. The study team was able to come up with several proposals for the improvement of the existing system after conducting a work study. The proposals are for the benefit of the workers, as it somehow eases their work and for the company, as it provides a means of increasing its market share by being able to provide more of the consumers' demands.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Twin Oaks Foods Corporation; Food industry and trade; Systems analysis